Tourism demand modeling and forecasting with artificial neural models: the Mozambique case study - Constantino, Hortêncio (2018)
This study aimed to model and forecast the tourism demand for Mozambique for the period from January 2004 to December 2013 using Artificial Neural Networks models. The number of overnight stays in Hotels was used as representative of the tourism demand. This variable was used as the output of the model.